Didge you sleep: a feasibility study of didgeridoo training for obstructive sleep apnea - Varun Badami; Nawaf Abaalkhail; Alex Petro; Cathy Alessi; Jennifer L. Martin; Maria Cristina Sanchez; Joseph M. Dzierzewski; Alex Suarez; Constance H. Fung (Sleep Science and Practice, 2024)
Abstract Intolerance of positive airway pressure therapy for obstructive sleep apnea is common. Upper airway muscle therapies show promise as alternative treatments. The didgeridoo, which is a musical instrument, can be used for upper airway muscle training. Our goal was to develop a group-based didgeridoo training program for obstructive sleep apnea. We conducted a proof-of-concept single-arm study consisting of a structured didgeridoo training regimen. We surveyed patients at a large medical facility about their interest in the program. We developed and tested a manual of procedures for conducting a 4-session group program conducted over 8 weeks that instructed participants on use of the Medical Didgeridoo. We also refined procedures for baseline and 4-month follow-up assessments, which included measures of daytime sleepiness and apnea–hypopnea index. Interviews were conducted at follow-up to obtain feedback about the program. Of the 56 survey respondents, 67% reported difficulty with positive airway pressure, expressed interest in participating in a structured upper airway muscle training program, and indicated that they would be willing to practice exercises for 30 min per day. After in-depth screening of 15 patients, we recruited five patients to participate in the structured training program; all five completed the program and were able to learn to play basic sounds on the provided instrument, and four stated they would continue to play the Medical Didgeridoo after completion of the program. Given the significant level of interest and excellent participation in the didgeridoo training program, it may be feasible to conduct a large-scale study to assess treatment response.